2008
DOI: 10.1002/jat.1339
|View full text |Cite
|
Sign up to set email alerts
|

Lung inflammation and thrombogenic responses in a time course study of Csb mice exposed to ozone

Abstract: Ozone is a well-known oxidant air pollutant, inhalation of which can result in oxidative stress, and lead to pulmonary inflammation. The aim of this study was to evaluate the time-course events after a single ozone exposure in transcription-coupled repair defective Csb and wild type mice. Mice were exposed for 3 h to 2 ppm ozone and biological parameters related to oxidative stress and inflammation were examined in the lungs at 0, 4, 9, 24 and 48 h after exposure. In addition the procoagulant and thrombomoduli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Furthermore, it is documented that a single O 3 exposure might induce significant biological response in TM level, inflammatory and pro-coagulant reactions in the lungs of mice [18]. Consistent with this study, we found that O 3 level was significantly associated with TF and TM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, it is documented that a single O 3 exposure might induce significant biological response in TM level, inflammatory and pro-coagulant reactions in the lungs of mice [18]. Consistent with this study, we found that O 3 level was significantly associated with TF and TM.…”
Section: Discussionsupporting
confidence: 91%
“…Findings of experimental studies suggest that exposure to air pollution may result in increase in TF and decrease in TM [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies show that genes related to innate immune signaling—in particular TNF receptors 1/2 and toll-like receptors 2/4—may modulate risk related to O 3 exposure, as well as associated genes including Nfkb1 (nuclear factor of kappa light polypeptide gene enhancer in B cells 1), Jnk1 (mitogen-activated protein kinase 8; Mapk8 ), Cd44 (Cd44 antigen), Myd88 (myeloid differentiation primary response gene 88), Iai (inter-α-trypsin inhibitor), Hsp70 (heat shock protein 70), Mmp9 (matrix metallopeptidase 9), and Nos2 (nitric oxide synthase 2, inducible) (Bauer et al 2011; Cho et al 2001, 2007; Fakhrzadeh et al 2002; Garantziotis et al 2009; Hollingsworth et al 2004; Kenyon et al 2002; Kleeberger et al 2000, 2001; Williams et al 2007; Yoon et al 2007). There is also toxicologic evidence indicating that genes involved in pro- and anti-inflammatory signaling and oxidative stress modulate the O 3 response, including interleukins Il10 , Il13 , and Il6 , and Cxcr2 [chemokine (C-X-C motif) receptor 2], Marco (macrophage receptor with collagenous structure), Csb (excision repair cross-complementation group 6), and Nqo1 (Backus et al 2010; Dahl et al 2007; Johnston et al 2005a, 2005b; Kooter et al 2008; Voynow et al 2009; Williams et al 2008). Taken together, this evidence suggests the complexity of the biological mechanisms underlying airway inflammation and airway hyperresponsiveness (AHR) as well as genetic susceptibility, as previously described by Bauer and Kleeberger (2010).…”
Section: Resultsmentioning
confidence: 99%
“…First of all, a procoagulant effect was observed in lung tissue as indicated by increased TF activity and thrombin generation upon DEE exposure. Increased thrombin generation is most likely the resultant of increased TF and decreased thrombomodulin expression, due to inflammatory stimulation [33]. Second, the overall plasma haemostatic balance was shifted towards a procoagulant state.…”
Section: Discussionmentioning
confidence: 99%